Communio Sanctorum - Kordero, Kristian (Likhaan: The Journal of Contemporary Philippine Literature, 2010)
Kamatayan ni Fray Diego Ang Bisyon ni Sor Purificacion sa Impiyerno Eskapularyo Laberinto Relikwaryo Jerusalem Katiyakan